The role of m5C methyltransferases in cardiovascular diseases - Wang, Yan-Yue; Tian, Yuan; Li, Yong-Zhen; Liu, Yi-Fan; Zhao, Yu-Yan; Chen, Lin-Hui; Zhang, Chi (Frontiers in Cardiovascular Medicine, 2023)
The global leading cause of death is cardiovascular disease (CVD). Although advances in prevention and treatment have been made, the role of RNA epigenetics in CVD is not fully understood. Studies have found that RNA modifications regulate gene expression in mammalian cells, and m5C (5-methylcytosine) is a recently discovered RNA modification that plays a role in gene regulation. As a result of these developments, there has been renewed interest in elucidating the nature and function of RNA “epitranscriptomic” modifications. Recent studies on m5C RNA methylomes, their functions, and the proteins that initiate, translate and manipulate this modification are discussed in this review. This review improves the understanding of m5C modifications and their properties, functions, and implications in cardiac pathologies, including cardiomyopathy, heart failure, and atherosclerosis.